2(х+1)/3-3х+7/12=5(2х+3)/8-2
2x+2/3-3x+7/12=10x+15/8-2
8(2x+2)-2(3x+7)=3(10x+15)-48
16x+16-6x-14=30x+45-48
x=1/4
Пошаговое объяснение:
2(х + 1)/3 - (3х + 7)/12 = 5(2х + 3)/8 - 2 | * 24
16(х + 1) - 2(3х + 7) = 15(2х + 3) - 48
16х + 16 - 6х - 14 = 30х + 45 - 48
10х + 2 = 30х - 3
10х - 30х = -3 - 2
-20х = -5
х = -5 : (-20)
х = 0,25
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
2(х+1)/3-3х+7/12=5(2х+3)/8-2
2x+2/3-3x+7/12=10x+15/8-2
8(2x+2)-2(3x+7)=3(10x+15)-48
16x+16-6x-14=30x+45-48
x=1/4
Пошаговое объяснение:
2(х + 1)/3 - (3х + 7)/12 = 5(2х + 3)/8 - 2 | * 24
16(х + 1) - 2(3х + 7) = 15(2х + 3) - 48
16х + 16 - 6х - 14 = 30х + 45 - 48
10х + 2 = 30х - 3
10х - 30х = -3 - 2
-20х = -5
х = -5 : (-20)
х = 0,25